"It wasn't about Me". Issue 2 (25th November 2022) - Wines, Megan
Abstract : This paper uncovers how Terrence McNally's 1998 gay passion play Corpus Christi braids together queerness and religiosity to highlight that queer people are also welcome at the "spiritual table." By bringing together his life experiences as a gay man who grew up in Texas with the biblical passion story, McNally highlights ways in which the Bible has been weaponized against gay men specifically, while at the same time creatively retelling Jesus's execution to undercut that weaponization.